Correlation Between SNPs at the 3'UTR of the FGF2 Gene and Their Interaction with Environmental Factors in Han Chinese Diabetic Peripheral Neuropathy Patients - Jiang, Guangyuan; Xiao, Gang; Luo, Chao; Tang, Zhaohua; Teng, Zhipeng; Peng, Xing (Journal of molecular neuroscience, 2021)
FGF2 is a neurotrophic factor that can act as a key regulatory molecule of neuroprotection, neurogenesis, and angiogenesis in various injuries. To explore the genetic background of the FGF2 gene on DPN development, this study analyzed the correlation between SNPs in the 3'UTR of the FGF2 gene and their interaction with environmental factors in DPN patients of Han Chinese nationality. Sanger sequencing was used to analyze the FGF2 genotypes at the rs1048201, rs3804158, rs41348645, rs6854081, rs3747676, rs7683093, rs1476215, and rs1476217 loci in 150 DPN patients, 150 NDPN patients, and 150 healthy control patients. Plasma FGF2 levels were measured in all subjects by using ELISAs. Subjects carrying the T allele at the rs1048201 locus in the FGF2 gene had a significantly lower risk of developing DPN compared with subjects carrying the C allele (OR = 0.43, 95% CI = 0.33–0.56, p < 0.01). Subjects with the G genotype at the rs6854081 locus had an exceptionally higher risk of developing DPN than subjects with the T allele (OR = 1.66, 95% CI = 1.39–1.89, p < 0.01). Individuals harboring the G allele at the rs7683093 locus had a markedly higher risk of DPN than patients with the C allele (OR = 1.63, 95% CI = 1.36–1.87, p < 0.01). Finally, individuals having the A genotype at the rs1476215 locus had a significantly higher risk of DPN than individuals carrying the T allele (OR = 1.82, 95% CI = 1.53–2.02, p < 0.01). There was an interaction between age and alcohol consumption and the SNP rs7683093. SNPs at rs1048201, rs6854081, rs7683093, and rs1476215 in the FGF2 3’UTR were strongly associated with plasma levels of FGF2 ( p < 0.05). SNPs at the rs1048201, rs6854081, rs7683093, and rs1476215 loci in the FGF2 gene were significantly associated with the risk of DPN. A possible mechanism is that these SNPs affect the expression level of FGF2 by interrupting the binding of microRNAs to target sites in the 3'UTR.